Empire and Catastrophe - Segalla, Spencer (University of Nebraska Press, 2021)
"Empire and Catastrophe examines natural and anthropogenic disasters during the years of decolonization in Algeria, Morocco, and France, and explores the ways in which environmental catastrophes both shaped and were shaped by struggles over the dissolution of France’s empire in North Africa. Four disasters make up the core of the book: the 1954 earthquake in Algeria’s Chélif Valley, just weeks before the onset of the Algerian Revolution; a mass poisoning in Morocco in 1959 caused by toxic substances from an American military base; the 1959 Malpasset dam collapse in Fréjus, France, which devastated the Algerian immigrant community in the town but which was blamed on Algerian sabotage; and the 1960 earthquake in Agadir, Morocco, which set off a public relations war between the United States, France, and the Soviet Union, and which ignited a Moroccan national debate over modernity, identity, architecture, and urban planning.